Application of earth observing-1 (EO1) advanced land imager (ALI) and hyperion data for porphyry copper exploration - Pour, Amin Beiranvand (2015)
This study evaluates the capability of Earth Observing-1 (EO1) Advanced Land Imager (ALI) and Hyperion data for lithological and hydrothermal alteration mapping. ALI and Hyperion images covering the Meiduk and Sar Cheshmeh porphyry copper mining districts, SE Iran were acquired for alteration and lithological mapping. Spectral angle mapper, linear spectral unmixing and mixture-tuned matched-filtering were tested to discriminate the hydrothermal alteration areas of porphyry copper mineralization from surrounding environment using shortwave infrared bands of ALI at regional scale. Analytical imaging and geophysics (AIG)-developed hyperspectral analysis processing methods were applied to visible and near infrared and shortwave infrared bands of Hyperion for mapping iron oxide/hydroxide minerals and clay mineral assemblages in hydrothermal alteration zones at district scale. Results indicated that the tested methods are able to yield spectral information for identifying vegetation, iron oxide/hydroxide and clay minerals, lithological units and discrimination of hydrothermally altered rocks from unaltered rocks using ALI data at regional scale. Supergene altered areas consisting of iron oxide/hydroxide minerals such as hematite, limonite, jarosite and goethite were detected using visible and near infrared bands of Hyperion. Phyllic, advanced argillic and propylitic alteration zones associated with porphyry copper mineralization were discriminated based on the identified alteration minerals such as sericite, kaolinite, illite, alunite, chlorite, epidote and calcite using shortwave infrared bands of Hyperion.